Pavlov's physiology factory : experiment, interpretation, laboratory enterprise - Todes, Daniel Philip (Johns Hopkins University Press, 2002)
"Russian physiologist and Nobel Prize winner Ivan Pavlov is most famous for his development of the concept of the conditional reflex and the classic experiment in which he trained a dog to salivate at the sound of a bell. In Pavlov's Physiology Factory: Experiment, Interpretation, Laboratory Enterprise, Daniel P. Todes explores Pavlov's early work in digestive physiology through the structures and practices of his landmark laboratory - the physiology section of the Imperial Institute of Experimental Medicine." "In Lectures on the Work of the Main Digestive Glands, for which Pavlov won the Nobel Prize in 1904, the scientist frequently referred to the experiments of his coworkers and stated that his conclusions reflected "the deed of the entire laboratory." This novel claim caused the prize committee some consternation. Was he alone deserving of the prize? Examining the fascinating content of Pavlov's scientific notes and correspondence, unpublished memoirs, and laboratory publications, Todes explores the importance of Pavlov's directorship of what the author calls a "physiology factory" and illuminates its relationship to Pavlov's Nobel Prize-winning work and the research on conditional reflexes that followed it."--Jacket